"By the time she got sick it was just kind of too late": A qualitative study on advanced care planning among bereaved lesbian, gay, and bisexual older women. (February 2022) - Valenti, Korijna G; Janssen, Leah M; Enguidanos, Susan; de Medeiros, Kate
Background: Lesbian, gay, and bisexual (LGB) older women have unmet communication needs around palliative and end-of-life care. Past research has found communication differences for LGB women patients. Consequently, older LGB women may experience healthcare communication barriers around advance care planning. Aim: To explore experiences of bereaved LGB older women to understand perspectives regarding advance care planning communication between clinicians, patients, and dyads. Design: Guided by queer gerontology as a theoretical framework, this qualitative descriptive study employed individual interviews with purposively recruited participants. Interviews were conducted in person using a semi structured protocol and analyzed using inductive thematic analysis. Setting/participants: Sixteen LGB women, age 60 years or older from across the United States who had lost a spouse/partner within the past 5 years. Results: Four main themes emerged from the transcripts, LGB older women: (1) experience unclear advance care planning communication and end-of-life care support from clinicians, (2) often avoid advance care planning discussions with spouse or partners, (3) lack of knowledge about palliative or end-of-life care, and (4) have more positive experiences when there is consistent communication with spouse or partner and clinicians during a spouse/partner's illness and end-of-life. Discussion: While certain experiences and opinions may reflect those of non-LGB older adults, novel advance care planning barriers exist for LGB older women. Greater understanding among clinicians is needed regarding advance care planning conversations with LGB dyads. We recommend four improvements in training, recognition, acceptance, and dyad-based communication interventions.